2014
DOI: 10.5194/acp-14-2923-2014
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of total hydroxyl radical reactivity during CABINEX 2009 – Part 1: field measurements

Abstract: Abstract. Total hydroxyl radical (OH) reactivity was measured at the PROPHET (Program for Research on Oxidants: PHotochemistry, Emissions, and Transport) forested field site in northern Michigan during the 2009 Community Atmosphere–Biosphere INteraction EXperiment (CABINEX). OH reactivity measurements were made with a turbulent-flow reactor instrument at three heights from the forest floor above (21 and 31 m) and below (6 m) the canopy at three different time periods during the CABINEX campaign. In addition to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
93
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(97 citation statements)
references
References 49 publications
2
93
2
Order By: Relevance
“…10 An exponential temperature dependence of the missing reactivity was observed during two campaigns carried out in the same North American forest, consistent with either primary biogenic emissions (Di Carlo et al, 2004) or with their oxidation products (Hansen et al, 2014). Some of the campaigns carried out in other forested environments also observed a similar trend (Kaiser et al, 2016;Mao et al, 2012;Zannoni et al, 2017), whereas others found no evidence for this correlation (Ren et al, 2006b;Sinha et al, 2010).…”
Section: Introductionmentioning
confidence: 63%
See 3 more Smart Citations
“…10 An exponential temperature dependence of the missing reactivity was observed during two campaigns carried out in the same North American forest, consistent with either primary biogenic emissions (Di Carlo et al, 2004) or with their oxidation products (Hansen et al, 2014). Some of the campaigns carried out in other forested environments also observed a similar trend (Kaiser et al, 2016;Mao et al, 2012;Zannoni et al, 2017), whereas others found no evidence for this correlation (Ren et al, 2006b;Sinha et al, 2010).…”
Section: Introductionmentioning
confidence: 63%
“…For instance, measurements taken during the INTEX-B campaign (Mao et al, 2009) found that the missing reactivity correlated with formaldehyde concentrations; the authors concluded that this indicated that the missing reactivity potentially arose from VOCs that formed formaldehyde upon oxidation. Similarly, measurements performed in a forest in Michigan during the CABINEX campaign showed good correlation between the missing reactivity and both isoprene and its oxidation products 15 (methyl vinyl ketone, MVK, and methacrolein, MACR) when the missing reactivity was highest (Hansen et al, 2014).…”
Section: Generating a Global Field Of Missing Reactivitymentioning
confidence: 99%
See 2 more Smart Citations
“…After publication of Mogensen et al (2011), several measurement and modelling papers have followed investigating the vertical dimension of the OH reactivity (e.g. Mao et al, 2012;Pratt et al, 2012;Hansen et al, 2014).…”
Section: Correction On Referencementioning
confidence: 99%